The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1590/1516-3180.2020.0272.r3.21072020
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of mental health among hospital workers in the COVID-19 pandemic: a cross-sectional study

Abstract: BACKGROUND: The rapid spread of the COVID-19 epidemic has led to extraordinary measures taken worldwide, and has led to serious psychological disorders. Healthcare professionals face greater severity of stress burden, due both to their direct contact with patients with the virus and to the isolation dimension of this outbreak. OBJECTIVE: To examine psychiatric disorders such as anxiety, depression and sleep disorders among healthcare professionals working in an emergenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 23 publications
5
28
0
Order By: Relevance
“…The high incidence of depression and anxiety among females may be explained by their concerns as mothers, wives, and caregivers about infecting their family members, including children, partners, or older people who live with them. This result supports similar evidence compiled by Araç et al, 2020. Other studies in SA, China and Italy have found that females are more likely to be depressed and anxious than males and relate the gender differences to the hormonal response to stress, as women's hormones increase both stress and anxiety responses (Al-Hanawi et al, 2020;Alzaid et al, 2020& Moccia et al, 2020.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The high incidence of depression and anxiety among females may be explained by their concerns as mothers, wives, and caregivers about infecting their family members, including children, partners, or older people who live with them. This result supports similar evidence compiled by Araç et al, 2020. Other studies in SA, China and Italy have found that females are more likely to be depressed and anxious than males and relate the gender differences to the hormonal response to stress, as women's hormones increase both stress and anxiety responses (Al-Hanawi et al, 2020;Alzaid et al, 2020& Moccia et al, 2020.…”
Section: Discussionsupporting
confidence: 91%
“…The literature has other studies with the same results (Araç, Dönmezdil, 2020, Asante, Li, Liao, Huang, Hao, 2019. Likewise, QoL is severely affected in all cases of psychiatric or physical disorders, and this is reflected in the scores on scales that measure QoL (Araç, Dönmezdil, 2020). Furthermore, in the present work, particular risk factors were more affected than others.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Table 2 presents the collected data with corresponding interpretation towards analysed sleep quality in healthcare givers. The analysed data indicate that working with COVID-19-affected patients is associated not only with a poorer sleep quality and insomnia symptoms, but also with mental health risks such as increased stress and burnout as well as a strong predisposition to mental disorders such as depression and anxiety [56,57,[59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77].…”
Section: Sleep Quality In the Healthcare Givers Under The Covid-19 Pandemic Conditionmentioning
confidence: 99%
“…We see that you have overlooked this topic. Although there were 9 original articles [3][4][5][6][7][8][9][10][11] from Turkey indexed in LitCovid between the dates specified in your study, we haven't seen any article about this topic among the selected articles. The study held in our hospital, namely Evaluation of the effect of COVID-19 pandemic on anxiety severity of physicians working in the internal medicine department of a tertiary care hospital: a crosssectional survey yielded that particularly female doctors and physicians who have elderly family members and family members with chronic medical conditions showed more severe symptoms of anxiety [3].…”
Section: Two Separate and Important Points That Should Not Be Forgottmentioning
confidence: 99%